Створення 3d моделі в програмному середовищі Blender 3D - Заєць, В. Ю. (ХНУРЕ, 2024)
This work is devoted to creating 3D models in Blender. Blender is a 3D computer graphics package that is used for 3D modeling and visualization - they are needed for various fields of activity. This work covers all stages of creating a 3D model from idea to final presentation.
Keywords: середовище Blender 3D; 3d модель